From plate to achievement: A structural model of how eating patterns influence learning motivation through the mediation of psychological well-being - Yoga Achmad Ramadhan; Iin Andriani; Silvia Eka Mariskha (Jurnal Psikologi Tabularasa, 2025)
Eating habits plays an important role not only in physical health but also in psychological well-being, which in turn can influence students’ learning motivation. However, studies that examine the relationship among these three variables simultaneously are still limited. This study aims to analyze the relationship between diet, psychological well-being, and learning motivation, as well as to test the mediating role of psychological well-being. The research used a quantitative approach with a survey design. The respondents were 227 students of SMAN 13 in Samarinda, selected using purposive sampling. The instruments included a diet questionnaire, the Indonesian adolescent psychological well-being scale, and the Academic Motivation Scale (AMS). Data analysis was carried out using Structural Equation Modeling Partial Least Squares (SEM-PLS) and mediation testing through bootstrapping with the PROCESS Hayes model. The results show that diet does not have a direct effect on learning motivation (p = 0.58), but it has a significant effect on psychological well-being (p < 0.001). Psychological well-being has a significant effect on learning motivation (p < 0.001) and fully mediates the relationship between diet and learning motivation (indirect effect = 0,0945; CI [0.025–0.0976]). These findings indicate that a healthy diet contributes to learning motivation through the improvement of psychological well-being. In conclusion, psychological well-being is a key factor that bridges the relationship between diet and learning motivation. This study recommends integrating healthy diet programs with psychological well being enhancement strategies in schools to support students’ academic achievement.